Factors Affecting Bond Ratings On Banking Companies On The Indonesia Stock Exchange, 2012-2016 - Fadilla Yadinanti; Daud Arifin; Rindi Andika (Britain International for Academic Research (BIAR) Publisher, 2022)
The purpose of this study aims to determine the factors that affect the level of liability in banking companies listed on the Indonesia Stock Exchange. Design/methodology - This research is very associative research. The type of data used in this study is secondary data obtained by accessing the BEI Website (www.idx.co.id). To collect data, researcher documentation used. This research is considered as a quantitative analysis. To analyze the data, the researcher used Normality Test, Multiple Linear Regression and Hypetheses Test (F Test and T Test) with a significance value of 5%. Findings – The results show that there are financial factors affecting the current ratio, debt to equity ratio, and return on assets and there are also non-financial factors that affect maturity and security towards the level of liability in Banking Companies. The t-test (partially) shows that there are factors that affect the current ratio, maturity, secure towards the level of liability, and not for the ratio of debt to equity and return on assets.